Operation of a Novel, Gravity-Powered, Small-Scale, Surface Water Treatment Plant and Performance Comparison with a Conventional Mechanized Treatment Plant - Marcin Sawczuk; Przemysław Kowal; Ruth E. Richardson (Applied Sciences)
This paper presents a novel small-scale system for drinking water treatment from surface waters, designed to rely on gravity as the only source of energy driving the treatment process. The pilot-scale setup, designed for a flow rate of 0.5 L/s, was tested at the Cornell University Water Filtration Plant (CWFP) for a total period of 5 months of operation. The experiments evaluated the influence of selected process parameters on system performance. The identified best operation practices were used to complete a comparative study against CWFP’s full-scale treatment process and to conduct a performance assessment in the context of various legislative landscapes. The objective of the work was to determine both the advantages and disadvantages of the proposed technology over established solutions. Over the study period, the average turbidity of the produced water was equal to 0.54 NTU. The pilot complied with the United States Environmental Protection Agency (US EPA) turbidity standard of <0.3 NTU 47.1% of the time and <1 NTU for 89.9% of the time, thus falling short of the standard of <0.3 NTU 95% of the time and <1 NTU 100% of the time. For 99.5% of the time, it complied with the World Health Organization turbidity guideline of <5 NTU for chlorination treatment. The benchmark conventional system outperformed the tested prototype, complying with the US EPA standards for the entire duration of the study. The tested process also generated a waste stream, which accounted on average for more than 10% of the total raw water volume.